Population Pharmacokinetics of Vancomycin and Meropenem in Pediatric Extracorporeal Membrane Oxygenation Support - Zylbersztajn, Brenda; Parker, Suzanne; Navea, Daniel; Izquierdo, Giannina; Ortiz, Paula; Torres, Juan Pablo; Fajardo, Cristian; Diaz, Rodrigo; Valverde, Cristian; Roberts, Jason (Frontiers in Pharmacology, 2021)
Objective: Describe primary pharmacokinetic / pharmacodynamic (PK/PD) parameters of vancomycin and meropenem in pediatric patients undergoing ECMO and analyze utilized dosing to reach PK/PD target Design: Prospective, multicentric, population PK analysis. Setting: Two hospitals with pediatric intensive care unit Patients: Pediatric patients (1 month - fifteen years old) receiving vancomycin and meropenem for empiric or definitive infection treatment while ECMO support. Measurements and Main Results: Four serum concentration were obtained for patients receiving vancomycin (n = 9) and three for meropenem (n = 9). The PK/PD target for vancomycin was a ratio of the area under the curve to the minimal inhibitory concentration (AUC/MIC) of >400, and for meropenem was 4 times above MIC for 50% of the dosing interval (fT50% > 4xMIC). Pharmacokinetic modeling was performed using PMetrics 1.5.0. We included 9 patients, with 11 PK profiles for each antimicrobial. The median age of patients was 4 years old (2 months - 13 years) and 45% were male. Creatinine clearance (CL) was 183 (30-550) mL/min/1.73 m2. The median dose was 13.6 (range 10-15) mg/kg every 6 to 12 h and 40 mg/kg every 8 to 12 h for vancomycin and meropenem, respectively. Two compartment models were fitted. Weight was included as a covariate on volume of the central compartment (Vc) for meropenem. Weight was included as a covariate on both Vc and clearance (CL) and serum creatinine was also included as a covariate on CL for vancomycin. The pharmacokinetic parameters CL and Vc were 0.139 +/- 0.102 L/h/kg and 0.289 +/- 0.295 L/kg for meropenem and 0.060 +/- 0.055 L/h/kg and 0.419 +/- 0.280 L/kg for vancomycin, respectively. Across each dosing interval 91 % of patients achieved the PK/PD targets for adequate exposure for meropenem and 63.6% for vancomycin. Conclusions: Pharmacokinetic/pharmacodynamic objectives for vancomycin were achieved partially with conventional doses and higher dosing with extended infusion were needed in the case of meropenem.